Inter-Program Debate Tournament 2007 - Botley, Simon (Universiti Teknologi MARA, Sarawak, 2007)
UiTM Sarawak's finest debaters turned out recently to compete in a bombastic battle of subtle rebuttals and a titanic struggle of wit and logic - otherwise known as the Inter-Programme Debate Tournament 2007. The competition was divided into English and Bahasa Melayu categories and took place over three days between 30th March and 1st April. Organised by the Debate Club, the contest was hard-fought by experienced debaters and novices alike, and it is hoped that new debaters and future UiTM champions will emerge from this tournament.